Experimental study of aging-induced cementation effect on permeability property of bentonites. Issue 1 (1st January 2023) - Ito, D.; Wang, H.; Komine, H.
Abstract: In geological disposal for high-level radioactive waste, bentonites are planned to be used as the buffer material surrounding radioactive waste in Japan. Bentonite-based buffer material requires low water permeation for delaying contact between groundwater and the waste. Because of the extremely long half-lives of radionuclides of the waste, several barriers including the buffer material are designed to maintain workability of the geological disposal facility for tens of thousands of years. However, in the disposal circumstances with high water pressure, high temperature and various groundwater chemistries, occurrence of cementation and consequently property changes of the bentonite in the buffer are concerned. Few studies are available to understand the effect of cementation on bentonite properties because of the difficulties of simulating long-term alteration process experimentally. From the viewpoint of natural analogues, cementation process of the buffer may be regarded as part of formation process of bentonite ore. Thus, in this study, permeability tests were conducted on three kinds of Na-type bentonite ores with different geological ages from respectively, Japan, USA, and China to see the influence of cementation on permeability of bentonites. For comparison, undisturbed and reconstituted specimens were prepared. The results show that difference of hydraulic conductivities of the undisturbed and reconstituted specimens for each ore is less than one order, and this difference seems not to correlate with the geological age of the ores. From these results, the influence of cementation on the hydraulic properties of bentonite buffer seems small. It may also be a counteracted result by cementation effects in terms of restriction of the swelling of montmorillonite and blockage of water flow paths.